Encyclopedia of Polymer Science and Technology 2002
DOI: 10.1002/0471440264.pst097
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation

Abstract: The dielectric properties of polymers, as complex permittivity ɛ(ω) and complex conductivity σ(ω), measured in the frequency range 10 −6 to 10 12 Hz, give information on (1) the reorientational motions of chain dipoles and (2) the translational motions of charged species (ions, electrons). The theory of dielectric relaxation and charge conduction is outlined for dipolar and electrolyte systems and experimental dielectric data for amorphous, crystalline and liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Individual Components: Poly(propylene oxide) (PPO). The background on the dielectric properties of polymers and other glass formers has been described in great detail in a number of books and key reviews. DRS studies of neat PPO have also been reported, , and hence our goal here is not to be comprehensive. The glass transition temperature of neat PPO is not a function of molecular weight ( T g = −68 °C as measured by DSC).…”
Section: Resultsmentioning
confidence: 99%
“…Individual Components: Poly(propylene oxide) (PPO). The background on the dielectric properties of polymers and other glass formers has been described in great detail in a number of books and key reviews. DRS studies of neat PPO have also been reported, , and hence our goal here is not to be comprehensive. The glass transition temperature of neat PPO is not a function of molecular weight ( T g = −68 °C as measured by DSC).…”
Section: Resultsmentioning
confidence: 99%
“…The dipolar response presents at high frequencies one or more secondary relaxations. These processes are followed in decreasing order of frequency by the glass–rubber relaxation. ,…”
Section: Introductionmentioning
confidence: 99%